2012
DOI: 10.3928/00989134-20120807-05
|View full text |Cite
|
Sign up to set email alerts
|

Bathing People with Dementia: When Education Is Not Enough

Abstract: This qualitative study describes health care assistants' (HCA) perceptions and experiences related to bathing people with dementia in residential care settings. Data were collected from three focus groups with 18 HCA participants from 12 different residential care facilities. HCAs constructed two definitions of a successful bath, which informed their choice of bathing strategies. Three themes emerged from the data analysis in regard to their bathing strategies: I Know You, I Am All Alone, and I Am Not Prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…Of the 16 high‐quality studies, study designs were reported as grounded theory (3), ethnography (2), phenomenology (1), soft systems approach (1) and interpretative description (1), or reported as content analysis (3), thematic analysis (2), or framework analysis (1) or did not name the methodological orientation (2). Papers reported qualitative data for observational studies ( n = 12) (Boltz et al, ; Bourret, Bernick, Cott, & Kontos, ; Coyer, O'Sullivan, & Cadman, ; Gaspard & Cox, ; Kitson, et al, 2013b; Kneafsey, Clifford, & Greenfield, ; Lafreniére, Folch, & Bèdard, ; Lomborg et al, ; Sjögren Forss, Nilsson, & Borglin, ; Taylor, Sims, & Haines, , ; Wardh, Hallberg, Berggren, Andersson, & Sorensen, ) and experimental studies ( n = 4) where new practices were introduced (French et al, ; Jensen et al, ; Robison et al, ; Thomas et al, ). Of these, two papers included patient data about a new nursing care method.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 16 high‐quality studies, study designs were reported as grounded theory (3), ethnography (2), phenomenology (1), soft systems approach (1) and interpretative description (1), or reported as content analysis (3), thematic analysis (2), or framework analysis (1) or did not name the methodological orientation (2). Papers reported qualitative data for observational studies ( n = 12) (Boltz et al, ; Bourret, Bernick, Cott, & Kontos, ; Coyer, O'Sullivan, & Cadman, ; Gaspard & Cox, ; Kitson, et al, 2013b; Kneafsey, Clifford, & Greenfield, ; Lafreniére, Folch, & Bèdard, ; Lomborg et al, ; Sjögren Forss, Nilsson, & Borglin, ; Taylor, Sims, & Haines, , ; Wardh, Hallberg, Berggren, Andersson, & Sorensen, ) and experimental studies ( n = 4) where new practices were introduced (French et al, ; Jensen et al, ; Robison et al, ; Thomas et al, ). Of these, two papers included patient data about a new nursing care method.…”
Section: Resultsmentioning
confidence: 99%
“…Within the five high‐quality studies about hygiene, findings indicated that nursing behaviours should include explanation of the content and purpose of hygiene care activities and should be tailored where possible to individual patients (Coyer et al, ; Gaspard & Cox, ; Kitson et al, 2013b; Wardh et al, ), such as considering patient wishes to use their own toiletries (Coyer et al, ). Patients recognised the impact of feeling clean on well‐being and integrity but reported the difficult balance between preservation and threats to integrity when receiving body care.…”
Section: Synthesis Of Nurse Behaviours Within Each Essential Care Areamentioning
confidence: 99%
See 3 more Smart Citations